Introduction Analysis Of Several Levels Of The Mercury (Hg) In Shells - Male, Yusthinus T; Nanlohy, Alberth Ch.; Asriningsih, Asriningsih (Indonesian Journal of Chemical Research, 2014)
Water pollution by metallic mercury (Hg) in Buru island as a result of mining activity people are very dangerous for marine life, firstly for Mollusca that was consumed by local communities. Therefore, it is needed to measure the levels of pollution Hg of shells. The research has been done on several types of shells, taken at several different points, those are: at the Namlea market, Arumbae market, and Latuhalat beach. The research’s method used Cold Vapour Atomic Absorption Spectrophotometry (CV-AAS). The results obtained by the concentration of metals Hg in Polla shells (Telebraria sulcata) 0.19240 mg/kg; Manis shells (Ruditapes variegatus) 0.27171 mg/kg; Ciput shells (Nerita polita) 0.31387 mg/kg; Keong shells (Thais aculeata) 0.05556 mg/kg; Tudung shells (Cellana radiata) 0.05922 mg/kg and Bapaco shells (Telescopium telescopium) 0.00183 mg/kg. Based on the results of this research, the mercury (Hg) concentrations of several types of shells which contain levels of Hg that low enough and has not exceeded the threshold set by WHO as big as 0.5 mg/kg. Even that there was small concentrations of metals, it can be acumulated in human’s body and can be fatal to the health of humans who consume shells.